Models of distribution of public transport correspondence - T. N. Sakulyeva (Управление)
The subject of this research is the theory of traffic flow modeling and modern transport infrastructure in cities and regions. The article discusses the classification and application of various models of correspondence on public transport routes – network, route, and multimodal. The paper carries out a comparative analysis of two route models: 1) based on the intervals, where input information about each route is limited to its tracking by the transport network graph, the sequence of stops, the times of movement between stops and the frequencies of movement of vehicles; 2) based on schedules, that use detailed information about the schedules of vehicles along routes (arrival time and departure time for each stop). The study concludes that in models based on schedules, it is possible to define not behaviour strategies, as in the case of models based on intervals, but specific paths for each correspondence. As a result of the analysis of multimodal models of organization of transport flows, the author came to the conclusion that the most popular at present are models of distribution of correspondence along multimodal routes.